1993
DOI: 10.1007/bf02552251
|View full text |Cite
|
Sign up to set email alerts
|

Are we overstressing water quality in urinary stone disease?

Abstract: A door to door survey of 38,805 persons from urban (9527) and rural (nontribal--19,716; tribal--9562) areas was carried out from 59 localities of Udaipur region to find out the prevalence of urinary stone disease. Simultaneously 118 water samples were also collected. The three sources of drinking water in these localities were tap, handpump and well and the prevalence of urinary stone disease in relation with the source of drinking water was 548.3, 303.4 and 189.9/1,00,000 population, respectively. All the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…One of the potential health effects of hard water that should be mentioned is the formation of urinary stones. However, some epidemiological studies did not confirm this relationship [62,63]. Currently there is no direct evidence that increased water hardness can cause adverse health effects [60], except for extremely high Mg water content (hundreds of mg·L −1 ) that cause diarrheal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential health effects of hard water that should be mentioned is the formation of urinary stones. However, some epidemiological studies did not confirm this relationship [62,63]. Currently there is no direct evidence that increased water hardness can cause adverse health effects [60], except for extremely high Mg water content (hundreds of mg·L −1 ) that cause diarrheal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, the testing of water from Guam wells found a calcium carbonate (CaCO 3 ) content ranging from 172 to 610 ppm, from the Fena Reservoir at levels of 90 to 124 ppm, and from the Ugum Reservoir at 40 to 92 ppm [ 17 ]. Drinking hard water has been associated with an increased risk of developing calcium urinary stones in one study [ 23 ], but not in others [ 8 , 9 , 10 ]. In one study, drinking water from private wells as opposed to municipal water had an estimated relative risk of 1.5 ( p < 0.01) for urinary stone formation; the effect could not be associated with calcium, magnesium or sodium concentrations [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Water hardness from public water supply systems is thought to be related to urinary stone disease, largely due to public perception. However, studies have not noted a link between water hardness or water quality and the incidence of urinary stone formation [ 8 , 9 , 10 ]. One study identified an increased risk of urinary stone disease and consumption of water from private wells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…En la región de Rockie la media de la DT fue 58 ppm, en la región de Carolina la DT fue de 13.3 ppm, comparada con nuestra media de DT de 485 ppm. 11,22 Aunque la Organización Mundial para la Salud no tiene valores de referencia recomienda 200 ppm como límite aceptable en la dureza total del agua empleada para consumo humano y 500 ppm como límite 24 La dureza total de todas las muestras de agua obtenidas en nuestro estudio excedió el límite aceptable establecido nacional e internacionalmente (200 ppm) y 20% de las muestras rebasaron el límite de tolerancia (500 ppm). Por otra parte, Kohri encontró una asociación positiva entre la relación magnesio/calcio del agua empleada para consumo humano y la prevalencia de los cálculos renales de estruvita en regiones de basalto y roca sedimentaria en Japón.…”
Section: Discussionunclassified